2013
DOI: 10.1073/pnas.1221312110
|View full text |Cite
|
Sign up to set email alerts
|

Imaging burst kinetics and spatial coordination during serial killing by single natural killer cells

Abstract: Cytotoxic lymphocytes eliminate virus-infected and cancerous cells by immune recognition and killing through the perforin-granzyme pathway. Traditional killing assays measure average target cell lysis at fixed times and high effector:target ratios. Such assays obscure kinetic details that might reveal novel physiology. We engineered target cells to report on granzyme activity, used very low effector:target ratios to observe potential serial killing, and performed low magnification time-lapse imaging to reveal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
115
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(124 citation statements)
references
References 38 publications
9
115
0
Order By: Relevance
“…However, recent studies proposed that lytic granule secretion may not even require prior polarization of the centrosome (24). Our data describing the sequential delivery of lethal hits with adjacent targets are consistent with a recently published study that investigated the kinetics of serial killing using the NK cell line, NK-92-MI (25). The authors reported that most serial killing events involved killing of adjacent targets, and they proposed that detachment from one target cell is directly regulated by subsequent attachment to the following target cell.…”
Section: Discussionsupporting
confidence: 91%
“…However, recent studies proposed that lytic granule secretion may not even require prior polarization of the centrosome (24). Our data describing the sequential delivery of lethal hits with adjacent targets are consistent with a recently published study that investigated the kinetics of serial killing using the NK cell line, NK-92-MI (25). The authors reported that most serial killing events involved killing of adjacent targets, and they proposed that detachment from one target cell is directly regulated by subsequent attachment to the following target cell.…”
Section: Discussionsupporting
confidence: 91%
“…To confirm that GB enters the mitochondria, a fluorescence resonance energy transfer (FRET)-based approach was used. HeLa cells were transfected with a GB-FRET reporter consisting of ECFP connected to EYFP with a linker containing a GB cleavage site VGPDFGR 29 that was targeted either to the cytosol or to the mitochondrial matrix (GB-cyto-FRET and GB-mito-FRET) (Supplementary Figures 1A and B). GB and perforin (P) treatment triggered a loss of FRET signal from the mito-FRET reporter with a similar kinetic to that of the cytosolic reporter, indicating that GB entered the mitochondrial matrix (Figures 1a-c and Supplementary Figures 1A and B).…”
Section: Resultsmentioning
confidence: 99%
“…4B; Conway et al, 2014Conway et al, , 2017Newman et al, 2011). Applications in cell proliferation (Harvey et al, 2008;Mochizuki et al, 2001), survival (Onuki et al, 2002;Tyas et al, 2000), signalling (Shih and Qi, 2017;Weitsman et al, 2016), immune cell activity (Choi and Mitchison, 2013;Li et al, 2016b), metabolism (Fehr et al, 2003;Imamura et al, 2009;Mächler et al, 2016;Okumoto et al, 2005) or migration (Seong et al, 2011;Wang et al, 2005) with a recent move to generate GEMMs of FRET biosensors for high-fidelity intravital imaging (Johnsson et al, 2014;Kamioka et al, 2012;Mukherjee et al, 2016;Nobis et al, 2017).…”
Section: Box 1 Subcellular Imaging Techniquesmentioning
confidence: 99%